(untitled) (Development Service Industry Management, 2025)
The article reveals the essence and significance of information technologies in enhancing the efficiency of enterprises’ marketing activities in the context of the digitalization of the economy. It analyzes the differences between traditional marketing and IT-driven marketing, defining their impact on the formation of competitive advantages and the transformation of business processes. The functional purpose of information technologies in marketing activities is outlined, and modern tools of their application are systematized, including CRM systems, Big Data analytics, communication automation, artificial intelligence, and analytical platforms. It is emphasized that the implementation of IT provides new approaches to managing customer relationships, optimizing business processes, personalizing offers, and evaluating the effectiveness of marketing campaigns in real time. Despite numerous advantages, the use of IT in marketing also involves certain risks that must be considered. These include cyber threats and data leaks, excessive dependence on technology, high financial costs of implementing advanced solutions, issues of confidentiality and ethical aspects of personal data collection, information overload due to processing large data volumes, staffing risks, as well as potential reputational losses in case of technical failures or incorrect personalization of communications. It is summarized that the effective use of information technologies in marketing activities requires a comprehensive approach, careful planning, data protection, and improving the digital competence of personnel. Despite some risks, IT enables enterprises to increase flexibility and responsiveness to market changes, improve forecasting accuracy, enhance the effectiveness of marketing decisions, and create long-term competitive advantages. The article emphasizes that information technologies are a key factor in the transformation of marketing strategies and determine the success of enterprises in the digital era.